2020
DOI: 10.1111/nana.12653
|View full text |Cite
|
Sign up to set email alerts
|

The politics of state celebrations in Belarus

Abstract: National celebrations have been defined as manifestations of collective identities that glorify the nation and strengthen the national community. However, the magnitude and design of celebrations in autocratic states indicate a different ideational function that these symbolic events play in an autocratic political system. Autocratic elites have the administrative capacity to distort everyday routines and impose ideological principles of how people participate in state celebrations. How citizens engage in offi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…In a study, completed just months before the political crisis, she pointed out that the more recent protests (2017), triggered by the so-called decree on social parasites (see above), were connected to the anniversary of the establishment of the Belarusian People’s Republic (March 25, 1918). This suggested that the “collective memory of alternative celebration dates, such as Dziady, 25 March and the anniversary of the Chernobyl disaster on 26 April” was not erased by the regime’s practices and could be used in the future to protest against the current government (Rohava, 2020: 16).…”
Section: Discussionmentioning
confidence: 99%
“…In a study, completed just months before the political crisis, she pointed out that the more recent protests (2017), triggered by the so-called decree on social parasites (see above), were connected to the anniversary of the establishment of the Belarusian People’s Republic (March 25, 1918). This suggested that the “collective memory of alternative celebration dates, such as Dziady, 25 March and the anniversary of the Chernobyl disaster on 26 April” was not erased by the regime’s practices and could be used in the future to protest against the current government (Rohava, 2020: 16).…”
Section: Discussionmentioning
confidence: 99%
“…By articulating Belarusian subjects as being incapable, and unwilling, to act outside of the governmentally sanctioned positions, such discourse dispossesses them from any qualities that might take the locus of control out of the government's hands: “initiative, individuality, diversity, creativity and choice” (Astapova, 2017, p. 65) and positions Belarusians as apolitical actors whose civic engagement is reduced to participation in carefully orchestrated rituals of state celebrations aimed to create “a reproducible image of public support for the authoritarian leadership” (Rohava, 2020, p. 898).…”
Section: Governmentally Sanctioned Belarusian Subject: Apolitical Sub...mentioning
confidence: 99%
“…Importantly, this acquiescence doesn't have to be active. Even during state celebrations, the most visible ritual of pledging allegiance to the state, the responsibilities for the majority of Belarusians do not go beyond mere presence (Rohava, 2020). What is required of citizens is not to alter their beliefs but to "act as if" (Wedeen, 1998), by enacting the prescribed subject positions for public presentation.…”
Section: Coronavirus As a Permissible Condition For Critical Juncture...mentioning
confidence: 99%
“…We have long understood from literature on nationalism that the material and ritualistic environment of the nation strengthens the understanding and imagination of the nation itself (Anderson, 2006(Anderson, [1983; Connerton, 1989;Durkheim, 1995Durkheim, [1912; Hobsbawm & Ranger, 1992), and recent scholarship has demonstrated how ritual and material forms of symbolic power are interpreted and reinterpreted in diverse and sometimes unexpected ways over time (Brubaker, 2004;Rohava, 2020;Rose-Greenland, 2013;Zahra, 2010;Zubrzycki, 2016). In scholarship on nationalism and culture, the physical and symbolic transformations of urban spaces and national rites have been of particular interest.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the efforts of elites, scholars have understood national symbols as reflective of national narratives and ideologies, demonstrating how changing urban landscapes and national rituals reflect new and sometimes competing conceptions of national culture and identity (Adams, 2010; Cummings, 2013; Diener & Hagen, 2013a, 2013b; de Freitas & Carvalho, 2022). Another line of scholarship has argued for the necessity of understanding the nation ‘from below’, illustrating the myriad ways the nation and its symbols are understood and contested (Güçler & Gür, 2021; Kosmarskaya et al, 2017; Liu, 2012; Rohava, 2020). While scholars have sought to bridge this epistemological divide by studying how national symbols are discursively constructed from above and below (e.g., Fox & Miller‐Idriss, 2008; Fox & Van Ginderachter, 2018; Liu, 2012; Nora, 1989; Sakki & Hakoköngäs, 2020), the processes that go into the production of national symbols are often left obscured.…”
Section: Introductionmentioning
confidence: 99%